2009
DOI: 10.1118/1.3121506
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic optimization of the scanning path of particle therapy beams

Abstract: Purpose: Quasi-discrete scannig is a delivery strategy for proton and ion beam therapy in which the beam is turned off when a slice is finished and a new energy must be set, but not during the scanning between consecutive spots. Different scanning paths lead to different dose distributions due to the contribution of the unintended transit dose between spots. In this work an algorithm to optimize the scanning path for quasi-discrete scanned beams is presented.Methods: The classical simulated annealing algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Shorter paths were obtained and consequently the treatment time was reduced. In a study by Pardo et al the delivered dose distribution using both algorithms (SA and zigzag algorithm) was quantified: results showed that a reduction in the transit particles was achieved for the paths obtained with the SA algorithm [8]. The main goal of this work is to compare the clinical/economical implications of using different scan path optimization strategies with what is currently being used (scan paths provided by Syngo RT Planning) in real treatment plans.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Shorter paths were obtained and consequently the treatment time was reduced. In a study by Pardo et al the delivered dose distribution using both algorithms (SA and zigzag algorithm) was quantified: results showed that a reduction in the transit particles was achieved for the paths obtained with the SA algorithm [8]. The main goal of this work is to compare the clinical/economical implications of using different scan path optimization strategies with what is currently being used (scan paths provided by Syngo RT Planning) in real treatment plans.…”
Section: Introductionmentioning
confidence: 96%
“…However, this leads to a sub-optimal use of the equipment, resulting in (i) a waste of particles spilled at each synchrotron pulse for non optimized paths and (ii) an increase in the treatment time due to the delay caused by the beam deflection activation. These reasons and the fact that shorter paths can reduce transit particles [8] motivated the search of competitive methods for the optimization of the scan path, aiming at cost-effective treatment delivery in quasidiscrete scanning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations